Empowering Students in Improving Knowledge of Healthy Toothbrushing Techniques in The Use of The Tongue Scraper - Purnamasari, Anisa; Saragih, Hondor; Pannyiwi, Rahmat; Puspitarini, Nurul Aisyiyah; Makualaina, Fenska Narly; Sipahutar, Pongki (International Journal of Health Sciences, 2024)
Tongue cleaning is a simple and quick procedure that helps remove organisms and debris on the tongue. Tongue cleaning can be done using a tongue scraper. This research was conducted to determine the correlation between the OHI-S index and tongue coating, and to explain knowledge regarding tongue hygiene and tongue scrapers in children at the Sejati Muhammadiyah Rappang Orphanage. The research subjects were children from the Sejati Muhammadiyah Rappang Orphanage who were on site at the time of the research and were willing to follow the research procedures. Dental hygiene is assessed by the OHI-S index and tongue examination is based on the tongue coating index. A total of 24 men and 16 women were given questionnaires before and after counseling. The results showed there was no significant relationship between the two indices (p=0.382). The distribution of questionnaire answers shows an increase in correct answers after providing counseling. However, based on education level and gender, there was no significant difference in knowledge regarding tongue hygiene and tongue scrapers (p=0.858, p=0.486). Non-significant differences were also seen in the comparison of groups that used and did not use a tongue scraper. It was concluded that there was no significant correlation between the OHI-S index and tongue coating. However, providing counseling was able to increase the knowledge of children at the Sejati Muhammadiyah Rappang Orphanage, although there was no difference in knowledge regarding tongue hygiene and tongue scrapers based on education level and gender.